OCORRÊNCIA DE ÁCARO Calacarus heveae NA CULTURA DA SERINGUEIRA. - RIBEIRO, Brenda Luciana Queiroz; TOSCANO, Luciana Cláudia; GANZELLA, Luiza Guidi; FERREIRA, Amanda Maria Frata; OLIVEIRA, Matheus Rodrigues; SILVA, Eduardo Paulino da Costa (ANAIS DO ENIC, 2024)
-